HOW LOCAL DEMOCRATIC BACKSLIDING? SINGLE CANDIDATE, PRAGMATISM AND UNCOMPETITIVE LOCAL HEAD ELECTION IN INDONESIA - Prianto, Andi Luhur; Yuslaini, Nina (JWP (Jurnal Wacana Politik), 2024)
This paper will examine how pragmatism has created rational choice behavior in candidate selection. Pragmatism has resulted in single candidates for local heads, which makes local democracy uncompetitive. The research method used is an explanatory approach that aims to explain how pragmatism as a rational choice behavior in the local government head election. Data were collected, compiled and analyzed using Nvivo 12 Plus software. The results showed that political parties as political institutions are very pragmatic in the selection of candidates for local heads. The incumbents utilized the support of almost all political parties based on clientelistic and programmatic relations. This has led the candidate selection process to prioritize pragmatic aspects, especially financial support, acceptability, and electability of candidates. The candidate selection process no longer determines ideological values at the official candidate selection process. Financial support for candidates has the highest priority for political parties in determining their endorsements in regional head elections. Meanwhile, the acceptability aspect refers to the dominant acceptance of all elites, cadres, and the mass base of supporters of the selected candidate. Electability is also a priority, although it is considered that electability trends are dynamic and able to change based on the level of competition. The behavior of political party elite actors and local head candidates eventually forms a rational choice pattern that makes local democracy backsliding.